(untitled) (Third Sector Social Economic Review, 2026)
This study develops a Carbon Communication Quality Index (C-Comm Index) to evaluate the credibility, transparency, and strategic coherence of carbon-related sustainability communication within sustainability marketing. Rising concerns about inconsistent or overstated environmental claims highlight the need for reliable assessment frameworks that do not depend on consumer surveys or firm-level performance comparisons. To address this gap, the study applies the Fuzzy-SWARA method to identify and weight the key criteria that shape the quality of carbon communication. A panel of experts in sustainability marketing, carbon accounting, and corporate communication evaluated dimensions such as transparency, evidence-based disclosure, data specificity, target measurability, greenwashing indicators, and narrative clarity. The fuzzy weighting procedure generated a coherent multi-criteria structure that aligns communication principles with expectations for rigorous carbon disclosure. The findings reveal which dimensions contribute most to credible and responsible carbon messaging in sustainability marketing. The resulting C-Comm Index provides academics and practitioners with a theoretically grounded and methodologically robust tool for assessing the reliability of carbon-related communication. By prioritizing expert judgment rather than self-reported or perception-based data, the study presents a replicable, low-cost, and ethics-exempt framework suitable for cross-sectoral applications, thereby contributing to research on sustainability communication, carbon transparency, and fuzzy multi-criteria decision-making.